Biochemical manifestations of the nervous tissue degradation after the blood-brain barrier opening or water intoxication in rats - Kozler, Petr; Sobek, Ondrej; Pokorny, Jaroslav (Neuro-endocrinology letters, 2016)
OBJECTIVES: The aim of the study was to determine changes of biomarkers of nervous tissue degradation in experimental model of osmotic blood-brain barrier opening or water intoxication and to find whether they correspond to changes in well defined clinical entities. METHODS: In the cerebro-spinal fluid taken via the suboccipital puncture, myelin basic protein (MBP ng/ml), neuron-specific enolase (NSE ng/ml) and TAU-protein (Tau pg/ml) were determined by ELISA in 19 controls and 29 experimental rats several hours or one week after the experimental intervention. RESULTS: Significant difference between the control and experimental groups was revealed only for the concentration of myelin basic protein. After the BBB opening, its level dramatically increased within hours and dropped back to control values within one week. Water intoxication induced only dilutional hypoproteinorachia. No significant changes were found in NSE and levels of TAU-protein were not detectable. CONCLUSION: 1. Increased permeability of cytoplasmic membranes induced by water intoxication does not alter any of monitored CSF biomarkers. 2. Osmotic opening of the BBB in vivo experiment without the presence of other pathological conditions leads to a damage of myelin, without impairment of neurons or their axons.
Keywords: proteiny tau; encefalitogenní základní proteiny; biologické markery; myelinová pochva; axony; Osmotic Pressure; krysa rodu Rattus; Myelin Sheath; osmotický tlak; Myelin Basic Protein; hematoencefalická bariéra; intoxikace vodou; tau Proteins; Axons; Biomarkers; zvířata; Rats; Animals; Water Intoxication; Blood-Brain Barrier